Africaines esclaves au Portugal : dynamiques d'exclusion, d'intégration et d'assimilation à l'époque moderne (XVe-XVIe siècles) - de Almeida Mendes, António (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2008)
Between 1440 and 1640, from 300,000 to 350,000 African slaves were forcefully moved from sub-Saharan Africa to the Iberic Peninsula. Mostly female and young, this population was led to Portugal, to live among different cultural practices-in a society where the smallest religious, ethnic, or cultural difference was a cause of exclusion. How did men and women of foreign origins and cultures share a life, and have children, with the Portuguese, without sharing the society's values? Through exclusion, integration, and assimilation, the African presence in Portugal, from the sixteenth century onwards, created a plural nation and complex identities.